2020
DOI: 10.1183/23120541.00539-2020
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing COVID-19 pneumonia in a pandemic setting: Lung Ultrasound versus CT (LUVCT) – a multicentre, prospective, observational study

Abstract: BackgroundIn this COVID-19 pandemic, fast and accurate testing is needed to profile patients at the emergency department (ED) and efficiently allocate resources. Chest imaging has been considered in COVID-19 workup, but evidence on lung ultrasound (LUS) is sparse. We therefore aimed to assess and compare the diagnostic accuracy of LUS and computed tomography (CT) in suspected COVID-19 patients.MethodsThis multi-centre, prospective, observational study included adult patients with suspected COVID-19 referred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 35 publications
7
56
0
1
Order By: Relevance
“…We have seen significant health disparities in COVID-19 outcome along geographic, socioeconomic, ethnic, cultural, and racial lines. [28][29][30][31] Portable imaging modalities such as bedside lung ultrasound circumvent these issues, while showing better accuracy than CXR and similar accuracy to CT. 10,[32][33][34][35][36][37][38][39][40][41][42][43] This may be considered as a viable alternative, especially in low-resource settings where CT might not be readily available.…”
Section: Ctssmentioning
confidence: 99%
“…We have seen significant health disparities in COVID-19 outcome along geographic, socioeconomic, ethnic, cultural, and racial lines. [28][29][30][31] Portable imaging modalities such as bedside lung ultrasound circumvent these issues, while showing better accuracy than CXR and similar accuracy to CT. 10,[32][33][34][35][36][37][38][39][40][41][42][43] This may be considered as a viable alternative, especially in low-resource settings where CT might not be readily available.…”
Section: Ctssmentioning
confidence: 99%
“…A large multicentric study by Yasukawa et al [ 26 ] found that LUS and CT have comparable diagnostic accuracy for COVID-19 pneumonia, with LUS reaching a sensitivity of 92% compared to PCR as a reference standard. In comparison to this study, the lower prevalence of lung abnormalities detected by LUS in our case series may be explained by the fact that a larger number of patients had very mild abnormalities on CT-scan or, anyhow, showed lesions that hardly reached the pleura, thus undetectable via LUS.…”
Section: Discussionmentioning
confidence: 99%
“…It was described as a preferred modality in Italy 52 during spring 2020, but it is not used as extensively in other geographies, mainly applied for patients with CT/CXR contraindications (children, pregnant women) and predestined to study solid organs unlike the lung. Some reported higher sensitivity than CXR in COVID-19 diagnosis 53 , or even comparable diagnostic accuracy to CT 54,55 , but the role of LUS for the COVID-19 pandemic is still actively debated in the literature 56,57,58 . A summary of the differences between the imaging modalities is provided in Table 2.…”
Section: Discussionmentioning
confidence: 99%